Psychological entitlement and its relationship to Personal Striving among educational counselors - Al-Jibori, Jala Abid (Al-Adab Journal, 2021)
When an individual believes that he deserves more than others in his surroundings, this belief will make him focus on his needs only and will reflect negatively in his dealings and his relationship with others through conflicts and divisions in his own environment, unless this belief is related to factors, performance or skills that push him towards (merit) which is considered the other side of the deserves, if this is found with the personal struggle that is positively linked with many positive psychological variables, then the performance and sense of the individual will be the pinnacle of positivity, and the individuals who have a personal struggle, perseverance, and clear achievement goals will have more prestige and moral value than others. If the research sample is represented by educational counselors who are an important part of the education system and a mainstay are not characterized by psychological merit, and who enjoy the high personal struggle, this will help build future generations. The success of an educational counselor in his work depends to a large extent on the extent of his personal struggle. If his struggle was high, his activity, perseverance, and achievement would be higher, and on the contrary, his activity would decrease. The current research aims to define psychological entitlement and its relationship to personal struggle among educational counselors and to know the correlation between them according to the gender variable (male and female counselors). In order to achieve the objectives of the current research, a scale of psychological merit and a scale of personal struggle were constructed, and indicators of validity, reliability, and discriminatory power were extracted. The two scales were applied to a sample of (200) male and female educational counselors from the Second Rusafa Education Directorate in Baghdad governorate, and after processing the data statistically, the research reached a set of results, including that the research sample did not enjoy psychological entitlement, and there were no statistically significant differences between male and female counselors in that. Although the sample being distinguished by personal struggle and in all its fields, there are no statistically significant differences between male and female educational counselors in this regard, and there is no correlation between the two variables. The researcher reached a set of recommendations, including preparing training and guidance programs that help improve and develop the personal struggle. The researcher proposes to conduct a study on the psychological entitlement and personal struggle of educational institution directors.